Polyurethane-based polymer electrolyte for lithium ion batteries: a review - Misenan, Muhammad Syukri Mohamad; Khiar, Azwani Sofia Ahmad; Eren, Tarik (WILEY, 2022)
For the past decade, lithium ion batteries have dominated the high-performance and mobile markets. Despite their domination in many sectors, the development of contemporary commercial lithium ion batteries is hampered by safety concerns such as leakage, burning and even explosions caused by organic liquid electrolytes with low boiling points. Polymer electrolytes are a promising option to solve or mitigate these issues. Polymer electrolytes have the advantages of low flammability, good flexibility, excellent thermal stability and high safety. Among others, polyurethane (PU) has attracted attention as a promising polymer electrolyte candidate for the future. The soft and hard segments of the polymeric chain given by polyols and isocyanates, respectively, give PU its characteristic multiphase structure. The PU's soft segment can operate as a polymeric solvent to solvate the cations, while the hard segment can be functionalized to retain a wider range of electrochemical stability, allowing the construction of polymer electrolytes in electrochemical devices. Numerous researchers have concentrated on developing high-performance PU-based polymer lithium ion batteries. Nonetheless, low lithium ion conductivity characteristics remain the most significant obstacles to its commercialization. In order to tackle the issues and improve the overall performance, both physical and chemical modifications are widely investigated to form a PU-based polymer electrolyte. In the light of this work, this review discusses PU as a polymer host and the approaches to increase its ionic conductivity, including polymer blending, copolymerization, crosslinking, filler addition, plasticization, salt dopant addition as well as the integration of PUs into polymeric ionic liquids. In this review, previous work regarding PU-based polymer electrolytes from 1988 to 2021 is discussed and summarized. (c) 2022 Society of Industrial Chemistry.
Keywords: polyurethane; polymer electrolyte; ionic conductivity; OIL-BASED POLYURETHANE; WATERBORNE POLYURETHANE; THERMOPLASTIC POLYURETHANE; POLY(ETHYLENE OXIDE); CELLULOSE NANOCRYSTALS; ELECTRICAL-PROPERTIES; MECHANICAL-PROPERTIES; TRANSPORT-PROPERTIES; SOLID ELECTROLYTES; BLEND POLYMER; Polymer Science